2008
DOI: 10.1136/bmj.a1938
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing "placebo treatments": results of national survey of US internists and rheumatologists

Abstract: Objective To describe the attitudes and behaviours regarding placebo treatments, defined as a treatment whose benefits derive from positive patient expectations and not from the physiological mechanism of the treatment itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
222
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(243 citation statements)
references
References 19 publications
13
222
1
7
Order By: Relevance
“…4,6 Patients' expectations can alter the course of illness, and surveys indicate that physicians often prescribe medications to promote placebo effects. [7][8][9] It is time to apply these findings to the ethics of shared decision-making (SDM), especially given SDM's inclusion in the Affordable Care Act of 2010. 10 The term SDM is often used inconsistently.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Patients' expectations can alter the course of illness, and surveys indicate that physicians often prescribe medications to promote placebo effects. [7][8][9] It is time to apply these findings to the ethics of shared decision-making (SDM), especially given SDM's inclusion in the Affordable Care Act of 2010. 10 The term SDM is often used inconsistently.…”
Section: Introductionmentioning
confidence: 99%
“…About 75% (68/90) of the practitioners opined in favor of psychological mechanism for A survey of GPs reported 86% prevalence of use of placebo at least once within the past year, and 48% using placebo treatments more than 10 times in the past year. [4] Another study reported 60% prevalence, [2] a national survey of U.S. internists and rheumatologists showed 55% prevalence [3] while a study of U.S. academic physicians reported 45% prevalence. [5] Our study showed higher (89%) prevalence of placebo prescribing; and of these, 80% reported using it more than 10 times a year.…”
mentioning
confidence: 99%
“…These findings are similar to those of U.S. studies. [3,5] Only 9% reported use of saline and distilled water injections, showing a trend of preferential use of "impure" placebo over "pure" placebo. [1] Limitations of this study are its small sample size and possible under-reporting by the practitioners.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C was thought to be a reasonable placebo particularly for this study due to the fact that it has not been suggested to mediate food selection (Cangiano et al., 1992, 1998; Morris et al., 1987). Conventional placebo pills that have been used in other pharmacological research were sugar pills (dextrose), over the counter analgesics as well as vitamins (Tilburt, Emanuel, Kaptchuk, Curlin, & Miller, 2008). Since caloric intake was the main focus of this study, the placebo used did not have any active ingredients that could have contaminated the data, or intervened with the transmission of tryptophan to the brain such as fatty acids (insulin spikes Golomb et al., 2010), or contain traces of tryptophan (e.g., rice, oats) (Gerhardt & Gallo, 1998).…”
Section: Methodsmentioning
confidence: 99%